Get Your Sexy Back : an Awareness Campaign seeking to educate youth in Singapore on the effects and consequences of binge drinking. - Fong, Yue Yeng. (2009)
This paper presents the collaboration between a group of four final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University, and local brewer, Asia Pacific Breweries Singapore. The communications campaign set out to increase awareness of the issue of binge drinking among youth aged 18 to 25 in Singapore. This paper includes conclusive research that shaped the direction of communication plans, detailed strategies and mechanics, and an evaluation of the team's efforts.